Design of a testbed for the study of system interference in space CMB polarimetry - Ghigna, T; Matsumura, T; Hazumi, M; Stever, SL; Sakurai, Y; Katayama, N; Suzuki, A; Westbrook, B; Lee, AT (Springer, 2020)
LiteBIRD is a proposed JAXA satellite mission to measure the CMB B-mode polarization with unprecedented sensitivity (σr∼0.001). To achieve this goal, 4676 state-of-the-art TES bolometers will observe the whole sky for 3 years from L2. These detectors, as well as the SQUID readout, are extremely susceptible to EMI and other instrumental disturbances, e.g., static magnetic field and vibration. As a result, careful analysis of the interference between the detector system and the rest of the telescope instruments is essential. This study is particularly important during the early phase of the project, in order to address potential problems before the final assembly of the whole instrument. We report our plan for the preparation of a cryogenic testbed to study the interaction between the detectors and other subsystems, especially a polarization modulator unit consisting of a magnetically rotating half-wave plate. We also present the requirements, current status and preliminary results.